Effects of Pasteurella multocida on Histopathology, miRNA and mRNA Expression Dynamics in Lung of Goats - Wencan Zhang; Zizhuo Jiao; Huixian Huang; Yanru Wu; Haotian Wu; Zhiyong Liu; Zhenxing Zhang; Qi An; Yiwen Cheng; Si Chen; Churiga Man; Li Du; et al. (Animals, 2022)
Pasteurella multocida (Pm) infection causes severe respiratory disease in goats. We investigated the effects of the Pm infection intratracheally on the histopathology, miRNA and mRNA expression dynamics in the lung of goats infected for 1, 2, 5 and 7 days. Pm infection caused fever, which significantly (p < 0.05) increased the body temperature of the goats from day 1 to 5. Haemotoxylin–eosin staining of the infected lung tissue showed characteristics of suppurative pneumonia with inflammatory cells infiltration and the lung structure destruction. During the Pm infection of the goats, compared with the control group, there were 3080, 3508, 2716 and 2675 differentially expressed genes and 42, 69, 91 and 108 significantly expressed miRNAs (|log2Fold Change| > 1, p < 0.05) in the Pm_d1, Pm_d2, Pm_d5 and Pm_d7 groups, respectively. Five miRNAs and nine immune-related genes were selected for confirmation by reverse transcription–polymerase chain reaction. The results indicated that the expression patterns of the miRNAs and genes were consistent with those determined by next-generation sequencing. The differentially expressed genes were enriched in cytokine–cytokine receptor interaction, cell adhesion molecules, complement and coagulation cascades, tight junction and phagosome Kyoto Encyclopedia of Genes and Genomes pathways and cytokine production, leukocyte migration, myeloid leukocyte migration, cell periphery, plasma membrane, extracellular region part, extracellular region and other Gene Ontology terms. The differentially expressed genes were mapped to marker genes in human and mouse lung cells. The results showed the presence of some marker genes of the immune cells. Compared with the CK group, five miRNAs and 892 common genes were differentially expressed in the Pm_d1, Pm_d2, Pm_d5 and Pm_d7 groups. The target relationships between the common 5 miRNAs and 892 differentially expressed genes were explored and the miRNAs involved in the host immune reaction may act through the target genes. Our study characterized goats’ reaction in the lung from histopathological and molecular changes upon Pm infection, which will provide valuable information for understanding the responses in goats during Pm infection.